New beginnings - Schwab, Victoria (New York, NY : Scholastic Inc., 2014)
Aria is a guardian angel and to earn her wings, she'll have to help three different girls. Aria's first mission is Gabby Torres. Gabby's brother is sick, and Gabby's been so worried about him for so long, she's forgotten who she is. When a new school offers her a fresh start, Gabby learns it's hard to make friends while keeping half her life a secret.
Includes an excerpt to Second chances.
730
Keywords: Guardian angels -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Cancer in children -- Juvenile fiction; Friendship -- Juvenile fiction